Correction to: Elemental Effects on Weld Cracking Susceptibility in Al xCoCrCu yFeNi High-Entropy Alloy (Metallurgical and Materials Transactions A, (2020), 51, 2, (778-787), 10.1007/s11661-019-05564-8) - Martin, Alexander C. (2021)
THE Acknowledgments in the original article are incomplete. Following is the updated text. This work was supported by the Institute of Materials Research (IMR) at The Ohio State University (OSU), and by the American Welding Society (AWS) Foundation. The authors also express their gratitude to Brady Soulivong, a high school student in the OSU Intern Program, which is hosted by the National Science Foundation IUCRC Materials and Manufacturing Innovation Research Center (Ma2JIC). Electron microscopy was performed at the Center for Electron Microscopy and Analysis (CEMAS) at The Ohio State University.